Studi Sosio-Legal Terhadap Ketertiban Dan Ketentraman Di Kabupaten Sidoarjo - Nalle, Victor Imanuel W. (Jurnal Hukum & Pembangunan, 2016)
Peace and order is a city needs. Achievement of these needs by local governments through regulatory instruments, namely the Regional Regulation. Sidoarjo regency set through Peraturan Daerah No. 10 of 2013. This study through socio-legal approach has been assessing the condition of the aspects that affect the implementation of the local regulation and constraints. This study shows that there are gaps in the understanding of the urgency of the substance of Peraturan Daerah No. 10 of 2013 for the public interest. In addition, conditions of law enforcement structures and culture of the people do not support the implementation of the Peraturan Daerah No. 10 of 2013. These conditions resulted in the emergence of obstacles to achieve peace and order indistrict of Sidoarjo.